Reforma al art. 345 del código orgánico de la función judicial a fin de establecer como competencia única de la justicia indígena el juzgamiento de contravenciones penales - Mondragón Martínez, Jaime Edison (2017)
The present research paper whose theme is "REFORMING ART 345 OF THE ORGANIC CODE OF THE JUDICIAL FUNCTION IN ORDER TO ESTABLISH AS A UNIQUE JURISDICTION OF INDIGENOUS JUSTICE THE JUDGMENT OF CRIMINAL COVENANTS" the present investigative thesis, reflects a scientific work, compared to the Legal and based on the criteria and arguments of the field results, with the purpose of demonstrating a work consiente of the problems and the reality of the indigenous communities of our Ecuador. For this reason I allow myself to make a brief general approach to the content of all the research with the aim that readers interested in reading or consulting in this thesis have an overview of the importance and content of the research work. In the Ecuadorian Criminal Law, different mechanisms and procedures have been envisaged for the resolution of conflicts, and referring to the evolution of criminal law, we have established different legal bodies, in order to maintain order and social peace. Consequently, the creation of normative bodies was indispensable and necessary. Thus, one of the most essential legal systems, such as the Organic Code of Judicial Function, will be dealt with later. On the other hand, it is important to state that our indigenous communities, peoples and nationalities have long owned and administered their own system of justice, based on their experience, ethical values, customs and traditions; In which justice is based on the application of sanctions in order that the individual who has committed a particular crime is inclined to admit their error, amend it and not do it again in the morning. The punitive system of indigenous justice, to a certain extent questionable, given that when any particular crime occurs within its territory, the accused are not subject to due process and, what is more, violates the principle of proportionality of the Penalty, thus opposing the current Constitution. The legislator, in issuing the Organic Code of Judicial Function, in article 345, establishes the competence of indigenous communities, peoples and nationalities to resolve conflicts. In relation to our investigation of a general way has been authorized to the indigenous justice the trial of crimes, without making any type of differentiation in matters nor classification of crimes; In such a way the procedure will be different from the Codes and laws of the ordinary justice, thus causing a serious social problem that affects the society. It is necessary and unavoidable that, without denying the possibility of the application of indigenous justice, it should be limited to the knowledge, prosecution and resolution of criminal offenses, which are slight and proportional to the sanctions that currently apply to the active subjects of the crime. The research problem is framed in the negative effects of the jurisdictional competence that the legislator has granted to indigenous justice, since it is not in complete harmony with the constitutional principles and institutions, as well as in order to respect and guarantee The subjective rights of the members of Ecuadorian society. It is a problem for the administration of justice, for the judges and for the victims, and for that reason it is necessary to solve this legal problem, on the other hand this investigation is within the respective limits. This thesis of Legal Research is structured as follows In the first place, different concepts related to indigenous justice, such as its objectives, definition of what indigenous law is, its characteristics, as well as a brief historical review of it, and then continue with a legal framework in which they are addressed Such as constitutional norms related to indigenous justice, customary law, the most common infractions in indigenous communities, which is the procedure to apply such justice, as well as the interference of ordinary justice in this field, To end up comparing the right to indigenous justice with that of other countries. Next, we find a doctrinal framework in which issues related to human rights are analyzed, their definition, characteristics and how to make them effective. We then continue to explain the methods and techniques used for the preparation of the present research, and thus to present the results obtained in the field research, this through survey, interviews and case analysis that have been given with respect To the problem investigated, after the field research was carried out, I verified the proposed objectives and contrasted the hypothesis, and then came to give the conclusions and recommendations that this problem merits and conclude by giving a draft of an indigenous justice law, which could Serve to bring it to the Assembly for its respective discussion and possible approval.